Left Ventricular End-Diastolic Diameter and Cardiac Mortality in Duchenne Muscular Dystrophy - Segawa K (Dove Medical Press, 2020)
Kazuhiko Segawa, 1 Norio Sugawara, 2 Kazushi Maruo, 3 Koichi Kimura, 4 Hirofumi Komaki, 5 Yuji Takahashi, 6 Masayuki Sasaki 7 1Department of Cardiology, National Center Hospital, National Center of Neurology and Psychiatry, Tokyo, Japan; 2Department of Psychiatry, Dokkyo Medical University School of Medicine, Tochigi, Japan; 3Department of Biostatistics, Faculty of Medicine, University of Tsukuba, Ibaraki, Japan; 4Department of General Medicine, The Institute of Medical Science, the University of Tokyo, Tokyo, Japan; 5Translational Medical Center, National Center of Neurology and Psychiatry, Tokyo, Japan; 6Department of Neurology, National Center Hospital, National Center of Neurology and Psychiatry, Tokyo, Japan; 7Department of Child Neurology, National Center Hospital, National Center of Neurology and Psychiatry, Tokyo, JapanCorrespondence: Kazuhiko SegawaDepartment of Cardiology, National Center of Neurology and Psychiatry, 4-1-1 Ogawahigashimachi, Kodaira, Tokyo 187-8551, JapanTel +81-42-341-2711Fax +81-42-344-6745Email ksegawa@ncnp.go.jpPurpose: This study aimed to examine weather left ventricular end-diastolic diameter (LVDd) could predict mortality from heart failure in patients with Duchenne muscular dystrophy (DMD) receiving standard cardio-protective therapies.Patients and Methods: One hundred thirty-three patients with DMD aged ≥ 10 years who underwent echocardiography from 2011 to 2015 were included in this study and retrospectively followed until August 2018. Patients were divided into two groups according to LVDd at initial echocardiography: ≤ 54 mm (Group 1: n=119) and ≥ 55 mm (Group 2: n=14). To identify factors other than LVDd that may affect heart failure-related mortality, Group 2 patients who developed no left atrial (LA) enlargement, moderate mitral regurgitation (MR), or pulmonary hypertension (PH) during the observation period (Group 2A: n=5) were compared with those who newly developed one or more of those complications (Group 2B: n=7). Clinical outcomes were all-cause mortality and mortality from heart failure.Results: Mean observation period was 5.5± 1.5 years in Group 1 and 4.4± 1.9 years in Group 2. A total of 14 patients (10.5%) died, including 6 of 119 (5.0%) patients in Group 1 and 8 of 14 (57.1%) patients in Group 2 (p< 0.001). Among these, 1 (0.8%) patient in Group 1 and 8 (57.1%) patients in Group 2 died from heart failure (p< 0.001). Group 2B patients had shorter survival compared to Group 2A patients (p=0.006).Conclusion: LVDd ≥ 55 mm is a predictive factor for mortality from heart failure in patients with DMD. Complications including LA enlargement, moderate MR, and PH were found to be predictive factors for mortality from heart failure in a short period.Keywords: cardiomyopathy, heart failure, echocardiography, left atrial enlargement, mitral regurgitation, pulmonary hypertension